Ingestion of Lead From Spent Ammunition: Implications for Wildlife and Humans 2009
DOI: 10.4080/ilsa.2009.0107
|View full text |Cite
|
Sign up to set email alerts
|

Lead Poisoning in Wild Birds in Europe and the Regulations Adopted by Different Countries

Abstract: Lead poisoning in birds was described in Europe at the end of the 19 th century, but the first epidemiological studies were not done until the second half of the 20 th century. So far, most work has focused on waterfowl and birds of prey, with very few reports evaluating the impact on upland game birds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(130 citation statements)
references
References 102 publications
2
121
0
7
Order By: Relevance
“…On the other hand, Kenntner et al (2003) did not observe such intersex relationships concerning mercury renal concentrations for German Goshawks, even though they recorded higher lead concentrations in the kidneys of females in comparison to males. That result may indicate a reduced share of small avian items in the prey pool of females, due to the females catching game birds of medium or large size, birds wounded by lead bullets (pheasants, ducks), or birds having swallowed such bullets by mistake (Mateo, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kenntner et al (2003) did not observe such intersex relationships concerning mercury renal concentrations for German Goshawks, even though they recorded higher lead concentrations in the kidneys of females in comparison to males. That result may indicate a reduced share of small avian items in the prey pool of females, due to the females catching game birds of medium or large size, birds wounded by lead bullets (pheasants, ducks), or birds having swallowed such bullets by mistake (Mateo, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There are different sources that can cause lead poisoning such as contaminated soil that can be found in the vicinity of mines and industrial plants (Garcia-Fernandez et al 1995, Beyer et al 2000 or sludge from sewage treatment facilities that is disposed in agricultural land (Pattee & Pain 1995) but the most common source causing lead toxicosis in birds is the ingestion of lead ammunition commonly used for hunting (Miller et al 2002, Fisher et al 2006. Birds of prey are one of the main groups affected by exposure to lead impacting several threatened species such as the White-tailed Eagle (Haliaeetus albicilla) and the Spanish Imperial Eagle (Aquila adalberti) (Mateo 2009). Vultures are particularly susceptible to lead ingestion from carcasses with embedded lead shot due to their scavenging nature and several cases of poisoned vultures have been recorded mainly in Spain (Mateo et al 1997, Gangoso et al 2009, Rodriguez-Ramos et al 2009 Hoyo et al 1994)] and showed extreme head and leg weakness, anorexia, dehydration and green faeces.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, mallard is a very useful biomonitoring species for Pb poisoning, since it holds a near worldwide and abundant distribution (Guitart et al, 1994), and the prevalence of Pb shot ingestion in this species is commonly moderate to high among waterfowl (Mateo, 2009). Here, the prevalence of Pb shot ingestion in the 2007-08 hunting season (28.6%, Fig.…”
Section: Risk For Waterbirdsmentioning
confidence: 88%